Evaluation of the antibacterial activity of mango ginger rhizome extracts against bacterial wilt pathogen Ralstonia solanacearum - M Anandaraj, R Karthika, D Prasath*, N K Leela, R Suseela Bhai, (Journal of Spices and Aromatic Crops, 2017)
The Indian mango ginger (Curcuma amada Roxb.) is a perennial rhizomatous herb with a raw mango flavour. It is resistant to bacterial wilt disease. In order to understand the disease resistance mechanism of mango gingerthe hexane, chloroform and methanol extracts (5, 10, 25, 50 and 100mg/ml) and essential oils (1%, 5% and 10%) were tested against the bacterial wilt pathogen Ralstonia solanacearum by agar well diffusion method. The hexane, chloroform and methanol extracts showed more or less the same level of antimicrobial activity with a zone of inhibition ranging from 3-9 mm. The essential oils exhibited a zone of inhibition ranging from 3-7 mm.The major constituents of the essential oils were ?-myrcene and ?-pinene. The results indicated that the rhizome of mango ginger may contain compounds that are toxic to the pathogen. The extracts of mango ginger could be explored further for developing a natural bactericide against R. solanacearum.